2004
DOI: 10.1098/rspb.2004.2773
|View full text |Cite
|
Sign up to set email alerts
|

Facultative adjustment of mammalian sex ratios in support of the Trivers–Willard hypothesis: evidence for a mechanism

Abstract: Evolutionary theory predicts that mothers of different condition should adjust the birth sex ratio of their offspring in relation to future reproductive benefits. Published studies addressing variation in mammalian sex ratios have produced surprisingly contradictory results. Explaining the source of such variation has been a challenge for sex-ratio theory, not least because no mechanism for sex-ratio adjustment is known. I conducted a meta-analysis of previous mammalian sex-ratio studies to determine if there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
323
5
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(361 citation statements)
references
References 63 publications
23
323
5
5
Order By: Relevance
“…The cost of sex ratio adjustment to an individual female will depend heavily upon the mechanisms involved (West & Sheldon 2002). Substantial evidence has been found in several mammalian species that sex ratio adjustment occurs at or near implantation (Cameron 2004;Sheldon & West 2004). Evidence thus points to some aspects of sperm selectivity or production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of sex ratio adjustment to an individual female will depend heavily upon the mechanisms involved (West & Sheldon 2002). Substantial evidence has been found in several mammalian species that sex ratio adjustment occurs at or near implantation (Cameron 2004;Sheldon & West 2004). Evidence thus points to some aspects of sperm selectivity or production.…”
Section: Discussionmentioning
confidence: 99%
“…The majority focus has been on the classical Trivers-Willard model (TWM, 1973), proposing that in species in which the variance in male reproductive success exceeds that of females, additional parental investment would benefit sons more than daughters, provided the offspring reproductive success is determined by phenotypic quality which in turn is at least partly determined by the level of maternal care during the juvenile stage (Maynard Smith 1980;Hewison & Gaillard 1999). Recent extensive meta-analyses of ungulate mammals showed that maternal condition around conception (rather than during gestation) was the best predictor of offspring sex ratio (Cameron 2004;Sheldon & West 2004), suggesting that TWM fits the ungulate model. However, there are a large number of studies failing to find any relationship between maternal condition and offspring sex ratio, including studies with very high quality data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is logically appealing and has been extensively tested in a wide variety of mammalian taxa (Cameron 2004;Sheldon & West 2004). In mammals, few studies have produced conclusive results either confirming or refuting this hypothesis, and the inconsistent results have proved difficult to interpret ( Festa-Bianchet 1996;Brown 2001;Cameron 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the production of sons and daughters is a key variable in life-history and evolutionary theory, with sex ratio at birth and hatching varying considerably (CluttonBrock & Iason 1986;Cameron 2004;Rosenfeld & Roberts 2004;Sheldon & West 2004). Adaptive hypotheses predict systematic variation in the sex ratio when the fitness returns of producing sons and daughters vary between individual parents ( Trivers & Willard 1973;Clark 1978).…”
Section: Introductionmentioning
confidence: 99%
“…For polygynous, sexually dimorphic species in which maternal investment influences offspring condition at weaning, they predicted that females in good condition would bias investment in favour of males. While considerable evidence for adaptive adjustment of sex ratios has accumulated for invertebrates (Godfray & Werren 1996), evidence of adaptive birth sex ratio biases in vertebrates is more highly disputed (Hewison & Gaillard 1999;Palmer 2000;Cockburn et al 2002;Komdeur & Pen 2002;Krackow 2002;West & Sheldon 2002;Cameron 2004;Sheldon & West 2004). Primates provide a particularly inconsistent body of data on sex ratio adjustment (Brown & Silk 2002;Silk & Brown 2004).…”
Section: Introductionmentioning
confidence: 99%